2019
DOI: 10.1038/s41598-019-47363-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis reveals correlation of long noncoding RNA ZEB1-AS1 with invasive profile in melanoma

Abstract: Melanoma is the deadliest form of skin cancer, and little is known about the impact of deregulated expression of long noncoding RNAs (lncRNAs) in the progression of this cancer. In this study, we explored RNA-Seq data to search for lncRNAs associated with melanoma progression. We found distinct lncRNA gene expression patterns across melanocytes, primary and metastatic melanoma cells. Also, we observed upregulation of the lncRNA ZEB1-AS1 (ZEB1 antisense RNA 1) in melanoma cell lines. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Transcriptome analysis can identify both coding and non-coding RNA, quantifying gene expression heterogeneity in cells, tissues, organs and even in the whole organism (50). Transcriptome analysis is important to investigate various processes (51) and it has been widely used to identify key factors in the progression of multiple diseases (27,52-53). Kim et al (52), using transcriptome analysis, identified Tensin 4 as a key effector of cetuximab and a regulator of the oncogenic activity of KRAS-mutant colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis can identify both coding and non-coding RNA, quantifying gene expression heterogeneity in cells, tissues, organs and even in the whole organism (50). Transcriptome analysis is important to investigate various processes (51) and it has been widely used to identify key factors in the progression of multiple diseases (27,52-53). Kim et al (52), using transcriptome analysis, identified Tensin 4 as a key effector of cetuximab and a regulator of the oncogenic activity of KRAS-mutant colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (27) reported the transcriptome profiling of brain myeloid cells, and identified an upregulation of integrin subunit α L, triggering receptor expressed on myeloid cells 1 and secreted phosphoprotein 1 in Western diet-induced obesity. Siena et al (53) performed a whole transcriptome analysis in melanoma and identified a correlation between the expression level of the long non-coding RNA ZEB1-AS1 with invasive ability of melanoma cells. These previous studies suggested that the transcriptome has become a reliable tool to identify key factors in the development and progression of various diseases (27,52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZEB1 antisense RNA 1 (ZEB1-AS1) is located in the opposite strand of gene Zinc Finger E-Box Binding Homeobox 1 (ZEB1). Transcription of both ZEB1-AS1 and ZEB1 is positively correlated in primary melanoma cells, when compared to melanocytes, and in metastatic melanoma cells, when compared to primary melanoma cells [ 177 ]. Apart from upregulating ZEB1, ZEB1-AS1 is suggested to sponge miR-1224-5p, which has been identified as a tumor suppressor in malignant gliomas.…”
Section: Competing Endogenous Rnas In Direct Interactions With Mirnasmentioning
confidence: 99%
“…Data analysis from TCGA confirmed the increased expression of ZEB1-AS1 in metastatic melanoma and its association with hotspot mutations in BRAF and RAS family genes. Additionally, enrichment analysis correlated ZEB1-AS1 with the gene expression of zinc finger E-box binding homeobox 1 ( ZEB1 ), an essential EMT marker, suggesting a possible role in melanoma invasiveness and phenotype switching [ 73 ].…”
Section: Lncrnas Modulate Melanoma Invasion and Metastasismentioning
confidence: 99%